Coherent Manipulation of Ultra Cold Atoms Towards Mobile Gravimetry - Dath, Hriday; Kannan, S.; Radhika, V. N. (European Journal of Applied Sciences, 2025)
Atom interferometry as a rapidly growing field has garnered a lot of interest in recent years for developing extremely accurate quantum sensors. It has been demonstrated by numerous research groups worldwide for a wide range of applications. In this work, we demonstrate the coherent manipulation of ultra-cold Rubidium (87Rb) atoms with Raman laser pulses in the transportable gravimeter setup based on cold atom interferometry developed at ISRO Inertial Systems Unit. The achievement of coherent manipulation is carried out by demonstrating the Rabi oscillations in ultra-cold ensemble. The obtained oscillation frequency is found to be very well matching with the theoretical calculation. Subsequently, we demonstrate Ramsey fringes by applying two π/2 pulses with a time gap depending on Rabi oscillation frequency.